Oxygen Vacancy Engineering in Photocatalysis. Issue 8 (31st March 2020) - Huang, Yanmei; Yu, Yu; Yu, Yifu; Zhang, Bin
Abstract : Photocatalysis, which converts natural solar energy into chemical energy, has emerged as one of the most appealing technologies in the past decades. However, photocatalytic performances are limited by the poor absorption of visible light, charge‐carrier recombination during migration, and a high energy barrier for activating reactants. Oxygen vacancies in semiconductive metal oxides are reported to be vital to improve their photocatalytic efficiency. In this regard, this review provides a concise overview of oxygen vacancies in transition metal oxides in photocatalytic systems, including their functions, construction strategies, characterization methods, and applications. Moreover, an outlook on the current challenges and promising opportunities in this field is provided. Abstract : Oxygen vacancy engineering in semiconductive metal oxides is reported to be vital to improve photocatalytic efficiency. This review provides a concise overview of oxygen vacancies in transition metal oxides in photocatalytic systems, including their functions, construction strategies, characterization methods, and applications. Moreover, an outlook on the current challenges and promising opportunities in this research area is provided.